SIMULTANEOUS INTERPRETATION AS A TYPE OF ORAL TRANSLATION - Fayziyeva S. Y. (Zeta Repository, 2023)
In order to establish a methodological foundation for the training of simultaneous interpreters at universities, this research explores simultaneous interpretation as a sort of oral translation in order to pinpoint its fundamental and distinctive characteristics. It defines its identical and particular qualities and contrasts simultaneous interpretation with other types of interpretation.